Application and research of marketing using automatic similar users extension technology in telecom industry - Xu ZHANG; Yang LIU; Lei HU; Xiaodong ZHAO; Haibin ZHANG (Dianxin kexue)
With the explosive development of data service,TSP(telecommunication service provider) has taken advantages of owing massive user data.It is a necessity for TSP to develop value added business using big data techniques which explores the data value.The traditional way of marketing utilizes rules or supervised classification method meets the challenge of low success rate and long data acquisition period.Therefore,a new service named Lookalike was proposed.The service supports precision marketing by integrating matric learning and deep learning efficiently based on telecom operators’ data characteristics.The Lookalike service decreases the artificial participation and enhances the efficiency and success rate of marketing activity.The enhancement of TTM (time to market) has been improved in many real programs and the success rate of marketing has increased absolutely.